2017
DOI: 10.1038/srep43637
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly and Anti-Amyloid Cytotoxicity Activity of Amyloid beta Peptide Derivatives

Abstract: The self-assembly of two derivatives of KLVFF, a fragment Aβ(16–20) of the amyloid beta (Aβ) peptide, is investigated and recovery of viability of neuroblastoma cells exposed to Aβ (1–42) is observed at sub-stoichiometric peptide concentrations. Fluorescence assays show that NH2-KLVFF-CONH2 undergoes hydrophobic collapse and amyloid formation at the same critical aggregation concentration (cac). In contrast, NH2-K(Boc)LVFF-CONH2 undergoes hydrophobic collapse at a low concentration, followed by amyloid formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 63 publications
2
51
0
Order By: Relevance
“…Our results show that the interaction of aggregates with the cellular membrane plays a role in the enhanced cellular stress leading to toxicity. We found that aggregates formed in the initial 0.5-1 h of incubation cause the most cellular stress (Figure 6), which correlates well with our cell viability and toxicity experiments ( Figure 7) as well as with previous toxicity studies [40,42,43] suggesting that aggregates formed at early stages of the aggregation process are the most powerful for inducing membrane permeability [8]. However, importantly, during the very early stages, the large majority of aggregates are nonfibrillar, but a dynamic population usually returns to monomers [54].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results show that the interaction of aggregates with the cellular membrane plays a role in the enhanced cellular stress leading to toxicity. We found that aggregates formed in the initial 0.5-1 h of incubation cause the most cellular stress (Figure 6), which correlates well with our cell viability and toxicity experiments ( Figure 7) as well as with previous toxicity studies [40,42,43] suggesting that aggregates formed at early stages of the aggregation process are the most powerful for inducing membrane permeability [8]. However, importantly, during the very early stages, the large majority of aggregates are nonfibrillar, but a dynamic population usually returns to monomers [54].…”
Section: Discussionsupporting
confidence: 90%
“…These values are in good agreement with previous toxicity studies of the Aβ peptide interacting with N2a cells, which reported viability values of almost 50% at a much higher peptide concentration (10 µM) than that used in our assay [42]. Regarding toxicity with other cell lines, it has also been shown Aβ42 aggregates at 10 µM that were previously incubated for 24 h at 37 • C, provoked a reduction in the cell viability of SH-SY5Y neuroblastoma cells by almost 20% [40], but the effect was even larger in primary neurons from E16 rat embryos in which Aβ42 aggregates at 20 µM caused a 65% reduction in cell viability [43]. In order to obtain additional information regarding the induction effect of different formed Aβ-647 aggregates on N2a neuronal cells, we took advantage of the fact that GG-DNBS is a dual sensor that is capable of not only simultaneously measuring levels of biothiols generated inside the cell but also detecting changes in the global levels of phosphate anions through the analysis of the fluorescence lifetime of the released fluorophore from the fluorogenic reaction, probe [41,44].…”
Section: Study Of Cellular Stress Using a Biothiol Probementioning
confidence: 68%
“…Despite of the reported variety of nanoparticulate assemblies of liquid crystalline order and hierarchical complexity, the investigations in which the structural organization of the lipid nanocarriers has been suggested as beneficial for curing of neurodegenerative disorders are scarce . The modifications of GPCR ligands and other neuropeptides by lipophilic anchors is suggested as a possibility for enhancement of the neuropeptide drug bioavailability.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the phenomena of self‐organization and study the aggregation mechanism of CFF in aqueous media, seven CFF solutions in a range of 0.3‐2.0 mmol⋅L −1 peptide concentrations were analyzed by steady‐state fluorescence spectroscopy. The critical aggregation concentration ( cac ) was assessed by the normalized intensity of the phenylalanine fluorescence emission at λ = 289 nm . In this way, the CFF cac (∼0.8 mmol⋅L −1 at 25 °C) was estimated from the crossover between linear fits corresponding to different emission regimes (Figure A).…”
Section: Resultsmentioning
confidence: 99%